A REVIEW ON AYURVEDIC PERSPECTIVE OF CAUSATIVE FACTORS LEADING TO STRESS AMONG INFORMATION TECHNOLOGY PROFESSIONALS - S, *Gopakumar; Shajahan, M.A. (International Journal of Ayurveda and Pharma Research, 2017)
Being a public health oriented medical science, Ayurveda has high responsibility in addressing job related health problems in different sectors. Stress has become an important aetiopathological factor in a good number of psychosomatic diseases. Stress, in general, is a physical, chemical, or emotional factor that causes bodily or mental tension and may be a factor in disease causation. In other words, stress is defined as the disruption of internal biological equilibrium triggered by external physical, mental or other types of stimuli. IT professionals are prone to develop stress and related health issues because of their high pressure job culture. Stress is never a single pathogenesis, but a wide spectrum of interconnected events, which may result in specific diseases affecting different systems. Ayurveda has a unique tool of Nidanapanchaka to unveil the aetiopathogenesis of any clinical condition. Ayurveda considers Nidana - causative factors as very important in the development of a disease. The nature and strength of Nidana determine the severity of every health problem. Here in the case of stress among IT professionals, multidimensional causative factors have defined role in different stages of pathogenesis. As per Ayurveda, treatment itself is avoiding the Nidana. A detailed understanding of these causative factors in Ayurvedic language will help to explore the stress related diseases in a better way. Classical Ayurvedic understanding of various causative factors related with stress among IT professionals will help to derive specific preventive and management protocols against stress and related clinical conditions.